2019
DOI: 10.1101/670661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune, Autonomic, and Endocrine Dysregulation in Autism and Ehlers-Danlos Syndrome/Hypermobility Spectrum Disorders Versus Unaffected Controls

Abstract: BackgroundA growing body of literature suggests etiological overlap between Ehlers-Danlos syndrome (EDS)/hypermobility spectrum disorders (HSD) and some cases of autism, although this relationship is poorly delineated. In addition, immune, autonomic, and endocrine dysregulation are reported in both conditions and may be relevant to their respective etiologies.AimsTo study symptom overlap in these two comorbid spectrum conditions.Methods and ProceduresWe surveyed 702 adults aged 25+ years on a variety of EDS/HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This form of EDS often presents with periventricular heterotopias, a structural anomaly that has also been noted in autism [ 69 , 70 ]. Raw data from our own previous study [ 16 ] likewise indicate that, compared to sex-matched controls, women with EDS/HSD report higher rates of epilepsy (5% vs. 1%), a figure that is similar to those with autism without intellectually disability (Mann–Whitney U, one-tailed, W = 17284.5, p = 0.042, EDS/HSD N = 367, control N = 98). (See Supplementary File S1, Table S6 for abbreviated raw data).…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 81%
See 4 more Smart Citations
“…This form of EDS often presents with periventricular heterotopias, a structural anomaly that has also been noted in autism [ 69 , 70 ]. Raw data from our own previous study [ 16 ] likewise indicate that, compared to sex-matched controls, women with EDS/HSD report higher rates of epilepsy (5% vs. 1%), a figure that is similar to those with autism without intellectually disability (Mann–Whitney U, one-tailed, W = 17284.5, p = 0.042, EDS/HSD N = 367, control N = 98). (See Supplementary File S1, Table S6 for abbreviated raw data).…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 81%
“…Preliminary work from Casanova et al [ 16 ] also suggests that autism and EDS/HSD co-occur within the same families. The researchers found that more than 20% of mothers with EDS/HSD reported having autistic children—a rate not significantly different from those reported by mothers who themselves are on the autism spectrum.…”
Section: Autism and Ehlers-danlos Syndrome Comorbidity And Familiamentioning
confidence: 99%
See 3 more Smart Citations